Motivations and barriers of entrepreneurs in Moscow and the Moscow region - Sulikashvili, Natalia; Kizaba, Godefroy; Assaidi, Abdelouahid (Business: Theory and Practice, 2021)
The main goal of this research is to examine the motivation of entrepreneurs from Moscow and the Moscow region in conducting entrepreneurial activity in present economic conditions, and to identify the obstacles slowing down this activity. For implementing this goal a survey of 63 small business owners was conducted. To collect the data, authors selected the ME (micro-enterprise), the SB (small business) and the SME (small and medium-sized enterprise). The actors questioned were entrepreneurs and more particularly the heads of companies running an ME, SB or SME in Moscow and its regions. Using research methods as factor analysis and Cronbach’s Alpha, a hierarchy of the different motives and entrepreneurial barriers were constructed. Investigation results show that regarding motivations of entrepreneurs, 4 components were obtained: extrinsic motivations composed of 4 items, intrinsic motivations composed of 6 items, motivations linked to independence and autonomy with 3 items and motivations related to the safety and well-being of the family with 3 items. In terms of barriers or obstacles encountered by Russian entrepreneurs, in regards with the literature review, we obtained 5 components: barriers of legitimacy consisting of 3 items, administrative barriers with 3 items, financial barriers with 2 items, managerial barriers with 3 items and finally competitive barriers with 3 items. The novelty of this study is to improve knowledge of the motivations and barriers that entrepreneurs in Moscow and its region encounter in the course of their activity.